Collecting vaginal discharge with or without speculum in diagnosing gynecological infections - Khodakarami, N; Mirzaalizade, M; Pazandeh, F; Alavi Majd, H (Advances in Nursing & Midwifery, 2008)
Background Currently, with the omission of speculum in vaginal examination, noninvasive methods to diagnose gonorrhea and chlamydia by urine tests are available. It is now possible to diagnose bacterial vaginosis, candidiasis and trichomoniasis by vaginal swabs directly without speculum examination. Purpose This quasi-experimental study was conducted to compare the results of two sampling methods with or without speculum of vaginal discharge in diagnosing gynecological infections. Methods 100 patients between 18-49 with vaginal discharge and other manifestations of vaginosis referring to gynecology clinic of Taleghani hospital were selected by convenience sampling method. One vaginal swab was used before examination with speculum and one during it to collect the discharge for diagnosing trichomoniasis, candidiasis and bacterial vaginosis. Both samples were observed under microscope by blind method and compared in terms of sensitivity. Results Sensitivities of discharge collection with and without speculum for diagnosing bacterial vaginosis, trichomoniasis and candidiasis were %81 and %71, 69% and %62.5, and %86 and %77 respectively with no significant difference. Agreements between the two methods for the diagnosis of bacterial vaginosis, trichomoniasis and candidiasis were 0.89, 0.85 and 0.72 respectively. Conclusion Gynecological infections can be detected without examination by speculum. This is helpful for those who fear from this type of examination and delay their visits. Keywords: Gynecological infections, Sexually transmitted disease (STD), Pelvic in flammatory disease (PID), Vaginitis